Composite material, production process and electronic component comprising composite material
By using a composite material of fluoropolymer matrix and BZT-αBXT type ceramic nanoparticles, the complex and cost-effective problems of existing piezoelectric materials production processes are solved, and improved ferroelectric and piezoelectric properties and simplified manufacturing processes are achieved.
Patent Information
- Application Number
- CN202411208728.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-08-29
- Filing Date
- 2024-08-30
- Publication Date
- 2025-03-04
AI Technical Summary
The production process of existing piezoelectric materials is complex and costly, making it difficult to achieve high performance and easy-to-produce new materials.
A composite material of a fluoropolymer matrix and BZT-αBXT type ceramic nanoparticles is used to form a film through spin coating and annealing processes to make electronic components.
Improved ferroelectric and piezoelectric properties are achieved, simplifying the equipment manufacturing process, reducing production costs, and improving the induction behavior and flexibility of the material.
Smart Images

Figure CN119552461A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a composite material having piezoelectric properties, a process for producing a thin film comprising the composite material, and an electronic component comprising the composite material. The electronic component may be, for example, a micro-electromechanical (MEMS) device, such as an acoustic sensor or actuator, in particular a microphone. Background Art
[0002] Recently, significant progress has been made in developing innovative materials for piezoelectric and acoustic-to-electric transduction, which have many applications, for example, in sound detection and recording, speed measurement, human activity detection, entertainment, information recognition, elderly care, and security.
[0003] Acoustoelectric conversion can also be used for small-scale energy harvesting and power supply. In fact, acoustic-to-electric conversion converts sound waves into electrical signals and can be obtained by exploiting various phenomena such as, for example, the piezoelectric effect.
[0004] Piezoelectric sound-to-electricity conversion, based on the deformation of materials caused by the vibration of sound waves, is particularly suitable for the development of flexible devices.
[0005] Conventionally, piezoelectric thin films are used to make acoustic-electric transducers. In this context, piezoelectric polymers have recently attracted particular interest, such as for example polyvinylidene fluoride (PVDF) and its copolymers, or composites based on a piezoelectric polymer matrix, which have shown acoustic-electric conversion capabilities.
[0006] These materials are particularly advantageous because they have superior flexibility compared to piezoelectric ceramics.
[0007] It is generally believed that PVDF, as a semi-crystalline polymer, has five polymorphs: α, β, γ, δ, and ε. The piezoelectric properties of PVDF are attributed to the presence of polar crystalline phases (including β and γ phases), and the β phase exhibits the largest electric dipole moment among all crystalline phases of the polymer. Therefore, one of the strategies for improving the piezoelectric properties of PVDF-based sensors, actuators, and energy harvesting transducers is to increase the β phase content.
[0008] Although the piezoelectric coefficients of PVDF and its copolymers are not as high as those of inorganic piezoelectric materials, their good flexibility, strength, chemical resistance, and biocompatibility make them promising piezoelectric candidates for self-powered sensors, microphones, and energy harvesting transducers.
[0009] PVDF-based composites containing piezoelectric ceramic fibers have also been prepared over the years in order to optimize PVDF-based devices and obtain higher sensitivity and higher output power, thus laying the foundation for various applications, for example, in the field of wearable devices and implants.
[0010] On the other hand, currently available materials (such as aluminum nitride, AlN) have long and complex production processes, which may envisage more than thirty deposition steps to form a layer of useful thickness in commercial applications.
[0011] Therefore, new piezoelectric materials with improved properties and ease of production are being sought. Summary of the invention
[0012] The present disclosure provides a new material with improved piezoelectric and ferroelectric properties which overcomes the disadvantages of the prior art and in particular allows easier manufacture of devices incorporating the material. Composite materials, processes for producing thin films, and electronic components obtained therefrom are provided.
[0013] A composite material includes: a fluoropolymer matrix; and a filler, which includes nanoparticles of a ceramic of the BZT-αBXT type, the nanoparticles being doped with at least one doping element, the at least one doping element being selected from the group consisting of Nb, La, Mn, Nd and W, wherein X is selected from Ca, Sn and Mn, and α is a molar fraction, the molar fraction being in the range between 0.10 and 0.90, provided that when X is Mn, the doping element is not Mn. A process for forming a thin film including the composite material is also provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0014] For a better understanding of the present disclosure, some embodiments of the present disclosure will now be described by way of non-limiting examples only, with reference to the accompanying drawings, in which:
[0015] Figure 1 The composite sample including PVDF and 25% 2% BCNZT (ie, (1-α)Ba(Zr (0.2-0.5y) Ti (0.8-0.5y) )Nb y O3-αBa 0.7 Ca 0.3 (Ti (1-y) Nb y )O3) X-ray diffraction (XRD) spectrum (spectrum), wherein α indicates the ratio between BZT and BCT, and y=0.02 indicates the degree of substitution of Nb relative to the sum of titanium (Ti) and zirconium (Zr);
[0016] Figure 2 illustrates a cross-section of a portion of a general MEMS device having a piezoelectric actuation structure;
[0017] Figure 3 The results of ferroelectric analysis of a thin film made of PVDF and a thin film formed of undoped PVDF and a BZT-BCT composite are shown;
[0018] Figure 4 Graphs show the results of ferroelectric analysis performed on thin films formed from composites of PVDF and 2% BCNZT, the composites of PVDF and 2% BCNZT being present in amounts of 15%, 20% and 25% of the total weight of the composite;
[0019] Figure 5 illustrates a graph of capacitance C as a function of frequency f in a composite material layer formed according to the present disclosure;
[0020] Figure 6 illustrates a graph of inductance Lp as a function of frequency f for different percentages of dispersed phase loading in a composite material layer formed according to the present disclosure;
[0021] Figure 7 illustrates a graph of phase Φ as a function of frequency f for different percentages of dispersed phase loading in a composite layer formed according to the present disclosure;
[0022] Figure 8 illustrates displacement s according to frequency f in a composite material layer formed according to the present disclosure;
[0023] Fig. 9 illustrates a graph of amplitude A versus frequency f for a composite material layer formed according to the present disclosure, the composite material layer being used for an ultrasonic detector (A_DUT) and an ultrasonic microphone (A_Mic), respectively; and
[0024] Fig.10 An example of an apparatus 20 using the present composite material is shown. DETAILED DESCRIPTION
[0025] The present description relates to a composite material comprising a fluoropolymer matrix and a filler formed of nanoparticles of a ceramic of the BZT-αBXT type, wherein X is selected from calcium (Ca), tin (Sn) and manganese (Mn), and α is a molar fraction selected in the range between 0.10-0.90 (inclusive), the nanoparticles being doped with at least one doping element selected from the group consisting of niobium (Nb), lanthanum (La), Mn, neodymium (Nd) and tungsten (W), with the proviso that when X is Mn, the doping element is not Mn. The nanoparticles have an average diameter comprised between 100 and 200 nm (inclusive).
[0026] Advantageously, the present composite materials have demonstrated improved ferroelectric and piezoelectric properties, as well as sensing behavior.
[0027] In particular, the presence of nanoparticles facilitates exchanges at the matrix-nanoparticle interface. Unlike the use of fibers, which favors film stiffening, nanoparticles allow for conductive paths that are essential for sensing properties and flexible films.
[0028] In particular, the size range of 100-200 nm maximizes the interface between the polymer and the filler. An average nanoparticle diameter greater than 200 nm does not ensure an effective interface between the polymer and the ceramic for charge transfer. In contrast, nanoparticles with an average diameter less than 100 nm tend to coalesce, hindering uniform distribution in the material.
[0029] The doping elements La, Mn and Nd can substitute elements at the positions of barium and calcium, while Nb and W can substitute elements at the positions of titanium and zirconium.
[0030] In one embodiment, the fluoropolymer is selected from the group consisting of polyvinylidene fluoride (PVDF) and copolymers thereof, in particular copolymers of PVDF with hexafluoropropylene (HFP) or with trifluoroethylene (TrFE).
[0031] In particular, PVDF and its copolymers may have a β-phase percentage mass fraction of at least 70%, more particularly between 86% and 99%, relative to the sum of the masses of the crystalline phases.
[0032] The BZT-αBXT type ceramic may be a barium zirconate titanate-barium calcium titanate (BZT-BCT) type ceramic, in particular (1-α)Ba(Zr (0.2-0.5y) Ti (0.8-0.5y) )Nb y O3-αBa 0.7 Ca 0.3 (Ti (1-y) Nb y )O3 type ceramic, wherein α indicates the ratio between BZT and BCT, and y=0.01-5% by weight of the total weight of the ceramic indicates the degree of substitution of Nb relative to the sum of Ti and Zr, in particular y=2% by weight of the total weight of the ceramic.
[0033] The ceramic (filler) content of the composite material is comprised between 10% and 25% by weight, in particular 20% by weight, of the total weight of the composite. Outside this range, the properties begin to decay up to a complete loss of the inductive behavior. Filler percentages greater than 25% cause the onset of bonding phenomena, the frequency of which increases with increasing filler percentages; such bonding phenomena increase the probability of causing electrical short circuits. Conversely, filler percentages less than 10% cause an inhomogeneous distribution of the filler in the matrix.
[0034] An embodiment of a process for producing a film formed from the above composite material is described below. Specifically, the process comprises:
[0035] a) subjecting a dispersion of ceramic nanoparticles in an organic fluoropolymer solution to a first spin coating step on a substrate at a speed comprised between 500 rpm and 1500 rpm (including 500 rpm and 1500 rpm), a second spin coating step at a speed comprised between 3500 rpm and 5500 rpm (including 3500 rpm and 5500 rpm); and a third spin coating step at a speed comprised between 8500 rpm and 12000 rpm (including 8500 rpm and 12000 rpm); and
[0036] b) subjecting the product of step a) to a first annealing step at a temperature comprised between 60°C and 70°C, inclusive, and to a second annealing step at a temperature comprised between 80°C and 90°C, inclusive.
[0037] Advantageously, this method allows for the formation of a homogeneous and uniform thin film.
[0038] In particular, a first spin coating step, for example, performed at 1000 rpm, results in the composite material being applied over the entire surface of the substrate; a second spin coating step, for example, performed at 4000 rpm, favors the first evaporation of the solvent, and a third spin coating step, for example, performed at 9000 rpm, favors the formation of the β phase, since it allows complete stretching of the PVDF chains and rotation of the H and F groups. In some embodiments, the substrate has a first surface opposite to the second surface, and the first surface of the substrate is completely covered by the composite material.
[0039] Furthermore, the first annealing step facilitates slow evaporation of the solvent, which makes the surface of the film uniform and homogeneous; the second annealing step allows the polymer chains to consolidate after complete evaporation of the solvent.
[0040] Due to its ferroelectric and piezoelectric properties, the composite material can be used to make electronic components such as acoustic sensors, especially microphones, energy harvesting transducers and microactuators.
[0041] Further characteristics will emerge from the following description of some purely illustrative and non-limiting examples.
[0042] Example 1
[0043] Preparation of composites according to the present disclosure
[0044] Preparation of 100 ml of 15 wt% PVDF solution
[0045] 17.78 g of PVDF powder was dissolved in a solution of 70 ml of dimethyl sulfone (DMSO) and 30 ml of acetone. The solution was placed on a magnetic hot plate and stirred at a temperature of 100° C. by magnetic stirring.
[0046] Preparation of BCT-BZT (2% BCNZT) nanoparticles doped with 2% Nb
[0047] BCN ZT ceramics are prepared by sol-gel technology, as described in EP 4074672 (US 2022 / 0332650). The precursor solution is then dried at 150°C and the powder is recovered.
[0048] Once recovered, the powders were homogenized and dry-milled using a planetary ball mill at 400 rpm for 4 hours. They were then calcined at 1400°C and wet-milled with ethanol (1 ml) for another 8 hours to obtain nanoparticles of the order of 100-200 nm.
[0049] Preparation of complexes
[0050] 2% BCNZT nanoparticles were added to the PVDF solution in different amounts (15 wt%, 20 wt%, and 25 wt% of the composite weight) and dispersed by ultrasonic treatment and stirring. The solution was left on a plate for about 10 days to stabilize.
[0051] Once stabilized, the solution is deposited on a substrate by spin coating to form a thin film. Three spin coating steps are performed.
[0052] The methodology used envisages three steps:
[0053] 1000 rpm every 10 seconds;
[0054] 4000 rpm every 30 seconds; and
[0055] 9000rpm every 60 seconds.
[0056] The sample was then placed on a plate at 70° C. for 10 minutes for complete evaporation and then on a plate at 90° C. for another 10 minutes for an annealing step before finally being cooled to room temperature T.
[0057] X-ray diffraction studies have been performed on the membranes to verify the formation of the PVDF phase.
[0058] Figure 1 An X-ray diffraction (XRD) spectrum of a composite sample including 25% of 2% BCNZT is shown; from this, it can be clearly seen that only β phase exists in PVDF.
[0059] The intensity of the 2% BCNZT peak also demonstrates the high homogeneity of the analyzed composites.
[0060] Example 2
[0061] Electrical Characterization
[0062] For electrical characterization, Figure 2 Sample 10 is shown.
[0063] The sample 10 includes: a semiconductor layer 11, such as a semiconductor layer of single crystal silicon; an insulating layer 12, such as an insulating layer of silicon dioxide; a lower electrode layer 13 formed by a TiO2 / Pt multilayer; a composite layer 14 of the present PVDF-BCNZT composite material; and a plurality of upper electrodes 15 of platinum (Pt).
[0064] In the sample used, the total thickness of the stack of layers 11 - 13 was 700 μm; the thickness of the composite layer 14 was 2 μm, and the thickness of the upper electrode 15 was 120 nm.
[0065] The sample was sprayed (Turbo Pump Thermal Evaporator K975X) with platinum to form the upper electrode and etched at the end to contact the lower electrode. Alternatively, a sputtering process can also be used to form the upper electrode.
[0066] For all measurements, the electrode was in contact with the metal tip via a manipulator on a handheld spindle probe. Electrical property testing and impedance spectroscopy were performed using a Keysight B1500A semiconductor device analyzer. Ferroelectric properties were studied using an Aixact TFA TF2000E analyzer, applying a 30V, 5kHz triangle wave signal to the sample.
[0067] Specifically, the samples tested were films formed using:
[0068] PVDF polymer only;
[0069] including composites of PVDF and BCT-BZT;
[0070] A composite comprising PVDF and 15% of 2% BCNZT;
[0071] A composite comprising PVDF and 20% of 2% BCNZT; and
[0072] A composite comprising PVDF and 25% of 2% BCNZT.
[0073] The results of ferroelectric tests are as follows Figure 3 and Figure 4 shown.
[0074] PVDF and PVDF_BZT-BCT films show more extensive ferroelectric properties associated with sensing behavior, which may be due to the emergence of conductive paths in the PVDF matrix.
[0075] Figure 4 The shape of the ferroelectric curve allows to highlight that the presence of Nb reduces the percolation paths in the film with narrower characteristics at the same voltage.
[0076] Due to the impedance measurements, interesting properties of the Nb-doped composites emerged. The samples were tested with the B1530 module of the B1500A, applying a 50mV AC signal to the samples and without DC polarization. Using this module, frequencies from 1kHz to 5MHz can be measured. These measurements confirm the dielectric properties of PVDF, such as Figure 5 shown.
[0077] like Figure 6 and Figure 7 As shown, the described complex also exhibits inductive properties for measuring impedance and phase.
[0078] Finally, the piezoelectric properties were measured by a laser vibrometer MSA-500 Micro System Analyzer (Polytec) on a cantilever device.
[0079] Membranes with different doping percentages were vibrationally tested using an MSA-500 Microsystem Analyzer (Polytec) to estimate the piezoelectric parameters. In particular, the device was analyzed by Fast Fourier Transform (FFT), a periodic chirp of 3 V was sent, and the displacement was measured using a laser vibrometer. This allowed the resonant frequency to be extracted. Figure 8 Shown is a graph of the displacement as a function of frequency exhibited by a device having a layer of a composite material comprising PVDF and 20% of 2% BCNZT.
[0080] Once the resonant frequency is extracted, the cantilever deflection can be estimated by setting the voltage and frequency near the resonance. According to the formula proposed by Mazzalai, the displacement and the corresponding value of the effective in-plane transverse piezoelectric coefficient e31f are shown in Table 1:
[0081]
[0082] where Y is Young's modulus, ν is Poisson's ratio, t Si is the thickness of the substrate (in Figure 2 In the example, the semiconductor layers 11-13), c f is the coverage factor of the electrode, x2 is the length of the piezoelectric active area, x1 is the length of the laser impact point, w(x2) is the deflection degree, and V is the amplitude of the applied sinusoidal signal.
[0083] Table 1
[0084]
[0085] Furthermore, since a resonant frequency close to 4 kHz was detected, the behavior of the various devices exposed to sound pressure was studied. Sound waves were sent from a loudspeaker to the cantilever and the response of the devices comprising the described composite material to a certified commercial microphone was studied using a Micro System Analyzer MSA-500. The measurements were carried out by driving the loudspeaker with an external sinusoidal signal of various frequencies in the audible range (from 20 Hz to 20 kHz). It was found that the response of the device comprising a composite material comprising PVDF and 20% of 2% BCNZT follows the signal detected by the microphone, with an amplitude that differs from that of the certified microphone by one tenth, as Fig. 9 As shown, where A_Mic refers to the amplitude measured in a certified commercial microphone, and A_DUT refers to the cantilever device using the present composite material.
[0086] Fig.10 An example of an apparatus 20 using the present composite material is shown.
[0087] The device 20 is, for example, a MEMS sensor or actuator; in particular a microphone.
[0088] The device 20 has a suspension structure 21 , here a cantilever, suspended above the cavity 30 .
[0089] The cavity 30 is formed in the substrate 31 and defines at the bottom the suspended structure 21. The suspended structure 21 may be integral with the substrate 31. The suspended structure 21 and the fixed structure 31 are, for example, of single crystal silicon.
[0090] An insulating layer 22 , for example of silicon dioxide, extends over the suspended structure 21 , and an actuation or detection structure 32 extends on the insulating layer 22 .
[0091] The actuation or detection structure 32 comprises: a lower electrode layer 23, for example formed by a TiO2 / Pt multilayer; a composite layer 24 of the present PVDF_2%BCNZT composite material; and a plurality of upper electrodes 25, for example upper electrodes of Pt.
[0092] Finally, it is evident that modifications and variations may be made to the composite materials and the production processes described and illustrated herein without departing from the scope of the present disclosure as defined in the claims.
[0093] A composite material comprises a fluoropolymer matrix and a filler consisting of nanoparticles of a ceramic of the BZT-αBXT type, wherein X is selected from Ca, Sn and Mn, and α is a molar fraction selected in the range between 0.10 and 0.90 (inclusive), the nanoparticles being doped with at least one doping element selected from the group consisting of Nb, La, Mn, Nd and W, wherein when X is Mn, the doping element is not Mn. In other words, in some embodiments, when X is Mn, the doping element is selected from the group consisting of Nb, La, Nd and W.
[0094] The nanoparticles have an average diameter comprised between 100 nm and 200 nm, inclusive.
[0095] The fluoropolymer is selected from the group consisting of polyvinylidene fluoride (PVDF) and copolymers thereof.
[0096] The copolymer is selected from the group consisting of a copolymer of PVDF and hexafluoropropylene (HFP) or a copolymer of PVDF and trifluoroethylene (TrFE).
[0097] Polyvinylidene fluoride (PVDF) and copolymers thereof have a β phase percentage mass fraction of at least 70% relative to the sum of the mass of the crystalline phase.
[0098] Polyvinylidene fluoride (PVDF) and its copolymers have a β-phase percentage mass fraction comprised between 86% and 99%, inclusive, relative to the sum of the masses of the crystalline phases.
[0099] The doping element is present in an amount comprised between 0.01% and 5% by weight, inclusive, of the total weight of the ceramic.
[0100] The ceramic content of the composite material is comprised between 1% and 70% by weight, inclusive, of the total weight of the composite.
[0101] A process for producing a thin film comprising a composite material comprises the following steps: a) subjecting a dispersion of nanoparticles in an organic phase fluoropolymer solution to a first spin coating step on a substrate at a speed comprised between 500 rpm and 1500 rpm (inclusive); a second spin coating step at a speed comprised between 3500 rpm and 5500 rpm (inclusive); and a second spin coating step at a speed comprised between 8500 rpm and 12000 rpm (inclusive). b) subjecting the product of step a) to a first annealing step at a temperature comprised between 60° C. and 70° C., and to a second annealing step at a temperature comprised between 80° C. and 90° C., wherein the nanoparticles are nanoparticles of a ceramic of the BZT-αBXT type, wherein X is selected from Ca, Sn and Mn, and α is a molar fraction selected in the range of 0.10-0.90, and the nanoparticles are doped with at least one doping element selected from the group consisting of Nb, La, Mn, Nd and W. In some embodiments, when X is Mn, the doping element is selected from the group consisting of Nb, La, Nd and W.
[0102] An electronic component includes a piezoelectric layer including the composite material.
[0103] The electronic assembly forms the acoustic sensor.
[0104] The acoustic sensor is a microphone.
[0105] The various embodiments described above can be combined to provide further embodiments. Aspects of the embodiments can be modified, if necessary to employ concepts of the various patents, applications and publications to provide yet further embodiments.
[0106] Based on the above detailed description, the above and other changes can be made to the embodiments. In general, in the appended claims, the terms used should not be interpreted as limiting the claims to the specific embodiments disclosed in the specification and claims, but should be interpreted to include all possible embodiments and the full range of equivalents to which these claims are entitled. Therefore, the claims are not limited by this disclosure.
Claims
1. A composite material comprising: Fluoropolymer matrix; as well as Filler, the filler comprising nanoparticles of a ceramic of the BZT-αBXT type, the nanoparticles being doped with at least one doping element, the at least one doping element being selected from the group consisting of Nb, La, Mn, Nd and W, wherein X is selected from Ca, Sn and Mn, wherein when X is Mn, the doping element is not Mn, and α is a molar fraction, the molar fraction being in the range between 0.10 and 0.90, wherein the nanoparticles have an average diameter between 100 and 200 nm, and wherein the filler is present in an amount between 10% and 25% by weight of the total weight comprised in the composite.
2. The composite material according to claim 1, wherein the fluoropolymer matrix is selected from the group consisting of polyvinylidene fluoride (PVDF) and copolymers thereof. 3 . The composite material according to claim 2 , wherein the copolymer is selected from the group consisting of a copolymer of PVDF and hexafluoropropylene (HFP) or a copolymer of PVDF and trifluoroethylene (TrFE). 4 . The composite material according to claim 2 , wherein the polyvinylidene fluoride (PVDF) and copolymers thereof have a β-phase mass fraction of at least 70% relative to the mass sum of the crystalline phase. 5 . The composite material according to claim 4 , wherein the polyvinylidene fluoride PVDF and copolymers thereof have a β-phase percentage mass fraction between 86% and 99% relative to the sum of the mass of the crystalline phase.
6. The composite material of claim 1, wherein the doping element is present in an amount between 0.01% and 5% by weight of the total weight of the ceramic.
7. The composite material of claim 1, comprising a ceramic content of 20% by weight of the total weight of the composite.
8. A method comprising: A film is formed, the film comprising a composite material having a fluoropolymer matrix and a filler, the filler comprising nanoparticles of a ceramic of the BZT-αBXT type, the nanoparticles being doped with at least one doping element selected from the group consisting of Nb, La, Mn, Nd and W, wherein X is selected from Ca, Sn and Mn, and α is a molar fraction, the molar fraction being in the range between 0.10 and 0.90, and wherein when X is Mn, the doping element is not Mn.
9. The method of claim 8, wherein producing the film comprises: The dispersion of nanoparticles in the organic phase fluoropolymer solution is subjected to a first spin coating step, a second spin coating step, and a third spin coating step.
10. The method according to claim 9, wherein: The first spin coating step is at a speed between 500 rpm and 1500 rpm; The second spin coating step is at a speed between 3500 rpm and 5500 rpm; and The third spin coating step is at a speed between 8500 rpm and 12000 rpm.
11. The method according to claim 9, further comprising: After said third spin coating step there is a first annealing step at a temperature between 60 and 70°C.
12. The method according to claim 11, further comprising: After said first annealing step a second annealing step at a temperature between 80 and 90°C is carried out.
13. An electronic component comprising a piezoelectric layer, the piezoelectric layer comprising the composite material according to claim 1.
14. A device comprising: a substrate having a first surface, the first surface being opposite to a second surface; as well as a layer of piezoelectric material, the layer of piezoelectric material completely covering the first surface of the substrate, the piezoelectric material comprising a fluoropolymer matrix, ceramic nanoparticles, and at least one doping element of Nb, La, Mn, Nd and W, the ceramic nanoparticles being of BZT-αBXT type, in: X is selected from Ca, Sn and Mn; The doping element is different from X; and α is the mole fraction, which is in the range between 0.10 and 0.
90.
15. The device of claim 14, wherein when X is Mn, the doping element is not Mn.
16. The apparatus of claim 14, wherein the ceramic nanoparticles comprise 2% by weight of the doping element.
17. The apparatus of claim 14, wherein the piezoelectric material comprises 15% by weight of the fluoropolymer matrix.
18. The device of claim 17, wherein the piezoelectric material comprises 15% to 25% by weight of the ceramic nanoparticles.
19. The device of claim 18, wherein the piezoelectric material comprises 20% by weight of the ceramic nanoparticles.
20. The device of claim 14, wherein the layer of the piezoelectric material has a thickness of 2 μm in a first direction from the layer of the piezoelectric material to the substrate.
Citation Information
Patent Citations
Method for the preparation of a lead-free piezoelectric material and precursor solution
EP4074672A1
Method for the preparation of a lead-free piezoelectric material and precursor solution
US20220332650A1